Improving Adolescent Knowledge on Mental Health and Balanced Nutrition through Meaningful Youth Participation: RAN PIJAR Health Heroes Experience in Bogor City - Sari, Nur Intan Kartika; Fajriyah, Afifathu Rahmah; Arimurti, Jazzy Dwi; Ramadhan, Muhammad Fajar; Wardana, Muhammad Trisna Kusuma (Insights in Public Health Journal, 2025)
Background: Adolescents aged 10–19 experience rapid development, making them vulnerable to nutrition and mental health issues; to address this, the RAN PIJAR program was implemented in Bogor using the Meaningful Youth Participation (MYP) approach through Health Heroes Facilitators to enhance their health knowledge. Methods: This quasi-experimental study used a one-group pre-test and post-test design involving 335 adolescents aged 15–18 years from nine senior high schools and one city-level scout organization in Bogor City. Health education sessions applied participatory methods such as Focus Group Discussions (FGDs), Human-Centered Design (HCD), and audiovisual materials. Wilcoxon signed-rank test was used due to non-normal data distribution. Results: After the intervention, the proportion of respondents with good knowledge on mental health and nutrition increased significantly from 50.1% with poor knowledge to 80.9% with good knowledge. A statistically significant improvement was observed (p = 0.000), with median rising from 50 (pre-test) to 90 (post-test). Conclusions: The intervention using the MYP approach effectively improved adolescent knowledge on mental health and balanced nutrition. The participatory and peer-led design created a relatable and engaging environment for adolescents. Future health education programs should adopt a sustainable, gender-equitable, and media-diverse approach and be integrated with school-based health initiatives such as School Health Units (UKS) and healthy canteens.